Hemangioma of the Buccal Mucosa of the Cheek Presenting as a Dermoid Cyst: A Case Report - Cameron Y. S., Lee (Journal of Clinical and Diagnostic Pathology, 2023)
This case report presents a 73-year old Asian female with a presumed dermoid cyst in the buccal mucosa of the left cheek that was visible and embarrassing to her. Histopathology revealed the mass to be consistent with a cavernous hemangioma. Hemangiomas are benign vascular tumors of mesenchymal origin. It is usually present at birth but can develop later in life. It commonly occurs in the head and neck region, but rarely in the oral cavity.
Keywords: head and neck; cheek; tumors